ΓH2AX foci assay in glioblastoma: Surgical specimen versus corresponding stem cell culture. (June 2021) - Riedel, Andreas; Klumpp, Lukas; Menegakis, Apostolos; De-Colle, Chiara; Huber, Stephan M.; Schittenhelm, Jens; Neumann, Manuela; Noell, Susan; Tatagiba, Marcos; Zips, Daniel
Highlights: GB specimens and gliospheres show pronounced radiation resistance. Floating gliospheres support the concept of radioresistance in cancer stem cells. Nestin expression indicates a high stem cell density in gliospheres. Gliospheres seem to be a good model to study radiation resistance mechanisms. Abstract: Aim: To assess radiation response using γH2AX assay in surgical specimens from glioblastoma (GB) patients and their corresponding primary gliosphere culture. To test the hypothesis that gliospheres (stem cell enriched) are more resistant than specimens (bulky cell dominated) but that the interpatient heterogeneity is similar. Material and methods: Ten pairs of specimens and corresponding gliospheres derived from patients with IDH-wildtype GB were studied. Specimens and gliospheres were irradiated with graded doses and after 24 h the number of residual γH2AX foci was counted. Results: Gliospheres showed a higher Nestin expression than specimens and exhibited two different phenotypes: free floating ( n  = 7) and attached ( n  = 3). Slope analysis revealed an interpatient heterogeneity with values between 0.15 and 1.30 residual γH2AX foci/Gy. Free-floating spheres were more resistant than their parental specimens (median slope 0.13 foci/Gy versus 0.53) as well as than the attached spheres (2.14). The slopes of free floating spheres did not correlate with their corresponding specimens while a trend for a positive correlation was found for the attached spheres and the respective specimens. Association with MGMT did not reach statistical significance. Conclusion: Consistent with the clinical phenotype and our previous experiments, GB specimens show low radiation sensitivity. Stem-cell enriched free-floating gliospheres were more resistant than specimens supporting the concept of radioresistance in stem cell-like cells. The lack of correlation between specimens and their respective gliosphere cultures needs validation and may have a profound impact on future translational studies using γH2AX as a potential biomarker for personalized radiation therapy.